A Phase I clinical trial of the knee to assess the correlation of gagCEST MRI, delayed gadolinium-enhanced MRI of cartilage and T2 mapping. Issue 90 (May 2017) - Wei, Wenbo; Lambach, Becky; Jia, Guang; Kaeding, Christopher; Flanigan, David; Knopp, Michael V.
Abstract: Purpose: Osteoarthritis (OA) is associated with the loss of glycosaminoglycan (GAG) during disease progression, which can be detected by glycosaminoglycan chemical exchange-dependent saturation transfer (gagCEST) MRI. Delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) is considered one of the standard methods for GAG quantification in vivo. This Phase I study assessed the correlation between gagCEST MRI and dGEMRIC in determining cartilage GAG concentration. Standard T2 mapping was used as a comparator with the two other methods. Materials and methods: Eight athletic volunteers with no known knee diseases were recruited in this study. The sagittal images of both knees in each volunteer were obtained by a 3 T MRI system. GAG concentration was calculated based on fixed charge density (FCD) within articular cartilage as calculated by T1 values obtained from dGEMRIC sequences. Magnetization transfer ratio asymmetry (MTRasym ) of the CEST spectrum at 1 ppm was determined with gagCEST MRI. T2 values were calculated using a multi-echo turbo spin echo (TSE) sequence. The Pearson correlations among MTRasym were calculated from gagCEST analysis. Results: There was moderate correlation (correlation coefficient r = 0.55) between dGEMRIC and gagCEST MRI results. T2 had a low correlation ( r = −0.30) with gagCEST and no correlation with dGEMRIC ( r = 0.003). Both gagCEST and dGEMRIC were able to distinguish between high GAG concentration cartilage compartments (higher than 210 mM) and low GAG cartilage compartments (lower than 210 mM). Conclusion: dGEMRIC was shown to be a more accurate and sensitive clinical imaging tool in evaluating cartilage GAG levels in vivo. While GagCEST showed less sensitivity to GAG concentration variations than dGEMRIC, further improvements may yet enable gagCEST to be a clinically robust methodology.